Review of the genus Encolapta Meyrick, 1913 (Lepidoptera: Gelechiidae: helariini) from China, with descriptions of six new species - Yang, Meiqing; Li, Houhun (Zootaxa, 2016)
Seventeen species of the genus Encolapta Meyrick, 1913 from China are reviewed. Six species are described as new: E. bifasciaria sp. nov., E. cornuta sp. nov., E. aciprojecta sp. nov., E. obliquata sp. nov., E. trapezoidea sp. nov. and E. lunata sp. nov.; the previously unknown female of E. marginans (Li et Zheng, 1998) is described for the first time; and one new combination, E. valvispinata (Li, 2002) comb. nov., is proposed. All these species are placed into two species groups based on morphological characters: the tegulifera-group and the epichthonia-group. Photographs of adults and genitalia are provided, along with a key to all the described Chinese species and two maps showing their localities.